Uric Acid: Friend or Foe? - Bin Wan Shuaib, Wan Muhammad Azfar; Mohamed Ismail, Nor Azlin; Abdul Manaf, Mohd Rizal; Othman, Hanita (IIUM Medical Journal Malaysia, 2022)
Introduction. Adverse Pregnancy outcomes (APO) continue to trouble physicians worldwide, and uric acid has become a marker of interest in its prediction. Despite this, the correlation of uric acid in the third trimester is rarely studied, and the reference value for normal uric acid levels in pregnancy has yet to be established. This study was done to evaluate the association of uric acid levels in the third trimester of pregnancy and the development of APO, specifically gestational hypertension (GH), pre-eclampsia (PE), gestational diabetes mellitus (GDM), small for gestational age (SGA) and to determine a cut-off value of serum uric acid levels for screening of the APO. Materials and methods. A retrospective observational study was conducted among 374 women who delivered at Pusat Perubatan Universiti Kebangsaan Malaysia (PPUKM) and developed the APO of interest and had serum uric acid levels taken during the third trimester of pregnancy. A cut off value of 309 µmol/L was used to assess the sensitivity and specificity in predicting the APO. Results. Associations are observed between 309 µmol/L and the development of GH (p<0.0005), PE (p<0.0005), GDM (p<0.0005), SGA (p=0.0264). Plotted ROC curves with cutoff point of 309 µmol/L demonstrated moderate predictive value of serum uric acid and the development of GH (AUC 0.639), PE (AUC 0.713), SGA (AUC 0.649) and low predictive value for GDM (AUC 0.4). Conclusion. Serum uric acid level of 309 µmol/L in the third trimester of pregnancy is a moderate predictor of GH, PE, SGA and a poor predictor of GDM. KEYWORDS: Uric acid; pregnancy trimester, third; pregnancy outcome